2018
DOI: 10.3390/rs10071163
|View full text |Cite
|
Sign up to set email alerts
|

GRACE-Based Terrestrial Water Storage in Northwest China: Changes and Causes

Abstract: Monitoring variations in terrestrial water storage (TWS) is of great significance for the management of water resources. However, it remains a challenge to continuously monitor TWS variations using in situ observations and hydrological models because of a limited number of gauge stations and the complicated spatial distribution characteristics of TWS. In contrast, the Gravity Recovery and Climate Experiment (GRACE) could overcome the aforementioned restrictions, providing a new reliable means of observing TWS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 77 publications
1
12
0
Order By: Relevance
“…The SWC was found to increase in Northwest China (Figure 5a). This is consistent with the study by Xie et al (2018), who found that the long-term variation trends of SWC were generally characterized by increasing in arid region of China, for example Northwest. However, precipitation in Northwest China showed no significant trend (Figure 5b).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The SWC was found to increase in Northwest China (Figure 5a). This is consistent with the study by Xie et al (2018), who found that the long-term variation trends of SWC were generally characterized by increasing in arid region of China, for example Northwest. However, precipitation in Northwest China showed no significant trend (Figure 5b).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the simulated soil water data had large systematic bias, which was elevated in the west by the complex topography and increasing land heterogeneity (Chen, Fan, et al, 2017; Chen, Zhang, et al, 2017). Most other studies were concerned with the spatio‐temporal variations of satellite derived‐soil water in some specific regions of China, for example Loess Plateau (Feng et al., 2017), Qing‐Tibet Plateau (Fan et al, 2018), Northwest China (Xie et al., 2018), Eastern China (Chen et al., 2016) and so on. As a country with large area, spatio‐temporal variations of soil water in different natural divisions have not been systematically compared and the main driving forces of soil water variations in different divisions have not been determined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extracted significant periodic signal is represented by the cone of influence (COI), where the phase discontinuity drops by e −2 at the boundary of the COI. The CWT is used to define the relationship between different geophysical processes-for example, the Baltic maximum sea ice extent and Arctic Oscillation index [14], land subsidence and GWS volume change [31], and climate, vegetation factors, and ∆TWS [32]. We employed the CWT to expand the groundwater volume changes and vertical displacements with corresponding time into a time-frequency space.…”
Section: Cross-wavelet Transform Between Depletion and Displacementsmentioning
confidence: 99%
“…The authors wish to make a correction to their paper [1]. After the final proofreading, they realized that the affiliation was incorrect due to their carelessness.…”
mentioning
confidence: 99%